2016
DOI: 10.1016/j.jag.2016.07.004
|View full text |Cite
|
Sign up to set email alerts
|

A practical algorithm for estimating surface soil moisture using combined optical and thermal infrared data

Abstract: a b s t r a c tSurface soil moisture (SSM) is a critical variable for understanding the energy and water exchange between the land and atmosphere. A multi-linear model was recently developed to determine SSM using ellipse variables, namely, the center horizontal coordinate (x 0 ), center vertical coordinate (y 0 ), semi-major axis (a) and rotation angle (Â), derived from the elliptical relationship between diurnal cycles of land surface temperature (LST) and net surface shortwave radiation (NSSR). However, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 45 publications
(47 reference statements)
1
20
0
Order By: Relevance
“…We use simply the observed solar radiation at 12:00 local time as the daily maximum solar radiation input is most likely to decrease the uncertainties for SSM retrieval, especially over larger areas. As reported in previous study (Leng et al, 2016), the linear relationship between the constant term and daily maximum solar radiation probably vary with regions. Hence, accurate determination of the constant term over larger areas is also a crucial task of estimating continuous SSM dataset.…”
Section: Calibration Strategiessupporting
confidence: 74%
See 2 more Smart Citations
“…We use simply the observed solar radiation at 12:00 local time as the daily maximum solar radiation input is most likely to decrease the uncertainties for SSM retrieval, especially over larger areas. As reported in previous study (Leng et al, 2016), the linear relationship between the constant term and daily maximum solar radiation probably vary with regions. Hence, accurate determination of the constant term over larger areas is also a crucial task of estimating continuous SSM dataset.…”
Section: Calibration Strategiessupporting
confidence: 74%
“…Obviously, because the model coefficients are obtained from numerous simulated data or through calibration processes, these time‐variable coefficients complicate the routine application of the SSM algorithm to generate SSM, especially for obtaining SSM over a long time series. Thus, to simplify the use of the model, a practical SSM retrieval algorithm under the assumption that all ellipse variables can be fixed, whereas the constant term varies daily and can only be determined using simple meteorological parameters in a prediction model, was developed recently (Leng et al, ). The new algorithm was written as follows: SSM=truen1¯×x0+truen2¯×y0+truen3¯×a+truen4¯×θ+p×Smax+q, …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the advantage of remote sensing observations, many efforts have been dedicated to determining the surface soil moisture for regional or even global applications [9][10][11][12][13][14]. Early field experiments demonstrated that passive microwave emissions and active microwave scatter are a function of the dielectric constant of the surface soil layer, and that the dielectric constant is related to the soil water content.…”
Section: Introductionmentioning
confidence: 99%
“…Wetlands also provide flood protection, protection from storm and wave damage, water quality improvements through the filtering of agricultural and industrial waste, and aquifer recharge [6][7][8]. Although wetlands play an important role in environmental processes and provide many ecological services for mankind, they are under increasing threats from climate change, dredge and fill operations, hydrologic variations, pollutant runoff, eutrophication, impoundments, and land modification, as well as the growing load placed on wetlands by agriculture, aquaculture, forestry, and development [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%